Adapting microalgae‐based strategies for sustainable green cities. Issue 10 (27th February 2022) - Chew, Kit Wayne; Show, Pau Loke
Graphical Abstract and Lay Summary: The adaptation of algae and microalgae as a renewable source in green cities will contribute to the overall environmental management. The cycle of microalgae growth reduces the carbon level, bioremediates wastewater and the final biomass can be transformed into important functional biomolecules. This perspective address the needs, benefits and challenges of implementing a microalgae green cities and its strategies.